Construction of the logarithm of a process on the matrix Lie group - Kovalchuk, L.V. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We construct the logarithm of a process taking values in a matrix Lie group as a process with values in the corresponding Lie algebra. This construction preserves some properties of the process (stochastic continuity, independence of increments, etc.).